2007
DOI: 10.1159/000103164
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome repatterning in three representative parrots (Psittaciformes) inferred from comparative chromosome painting

Abstract: Parrots (order: Psittaciformes) are the most common captive birds and have attracted human fascination since ancient times because of their remarkable intelligence and ability to imitate human speech. However, their genome organization, evolution and genomic relation with other birds are poorly understood. Chromosome painting with DNA probes derived from the flow-sorted macrochromosomes (1–10) of chicken (Gallus gallus, GGA) has been used to identify and distinguish the homoeologous chromosomal segments in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(102 citation statements)
references
References 47 publications
6
96
0
Order By: Relevance
“…Larkin et al (2009) suggested that homologous synteny blocks and evolutionary breakpoint regions are subject to different evolutionary pressures. As further avian genomes are published, especially those with atypical karyotypes (for example, Falconiformes and Psittaciformes (de Oliveira et al, 2005(de Oliveira et al, , 2010Nanda et al, 2007;Nishida et al, 2008;Nie et al, 2009), we will be able to test the hypothesis that blocks of ordered genes have been preserved through evolution, and that these are reflected in the syntenic blocks seen here. Further species that have been of interest in zoo-FISH studies and would thus be likely candidates for studies in addition to the Falconiformes and Psittaciformes mentioned above include other Galliformes (Shibusawa et al, 2004a, b) and a range of species from orders such as Anseriformes and Passeriformes (Guttenbach et al, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…Larkin et al (2009) suggested that homologous synteny blocks and evolutionary breakpoint regions are subject to different evolutionary pressures. As further avian genomes are published, especially those with atypical karyotypes (for example, Falconiformes and Psittaciformes (de Oliveira et al, 2005(de Oliveira et al, , 2010Nanda et al, 2007;Nishida et al, 2008;Nie et al, 2009), we will be able to test the hypothesis that blocks of ordered genes have been preserved through evolution, and that these are reflected in the syntenic blocks seen here. Further species that have been of interest in zoo-FISH studies and would thus be likely candidates for studies in addition to the Falconiformes and Psittaciformes mentioned above include other Galliformes (Shibusawa et al, 2004a, b) and a range of species from orders such as Anseriformes and Passeriformes (Guttenbach et al, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…Agapornis roseicollis karyotype has the lowest diploid number found in Psittaciformes, and an unusual high number of macrochromosomes (ten autosome pairs), suggesting that several fusion events have conformed this karyogram (Nanda et al, 2007). It is difficult to propose karyological relationships between this species and other parrots.…”
Section: Callocephalon Fimbriatum and The Cockatoo Familymentioning
confidence: 88%
“…Present day availability of some avian genome sequences, or techniques based on chromosome painting with DNA probes have improved our ability to reconstruct chromosome evolutionary changes (de Oliveira Furo et al, 2015;Nanda, Karl, Griffin, Schartl, & Schmid, 2007;Seibold-Torres et al, 2016). Interchromosome evolutionary changes have been considered to occur rarely during avian diversification suggesting that mechanisms exist to preserve a static overall karyotype structure (Romanov et al, 2014).…”
Section: Avian Cytogenetic Considerationsmentioning
confidence: 99%
See 2 more Smart Citations